2020
DOI: 10.1111/cod.13687
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and incidence of contact dermatitis among hairdressers in north‐eastern Italy

Abstract: Background: Hairdressers are at high risk of contact dermatitis (CD) due to skin exposure to numerous irritants and haptens in hair products in combination with frequent wet work. Objectives: To investigate the characteristics and incidence of CD among hairdressers in northeastern Italy. Methods: A total of 324 hairdressers who had been examined and patch tested in northeastern Italy from 1996 to 2016 were retrospectively identified, and compared with 9669 matched controls. Sensitization to allergens of the ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 65 publications
(222 reference statements)
7
25
1
Order By: Relevance
“…This is in accordance with the previous findings that hair dye product ingredients such as p ‐phenylenediamine and toluene‐2,5‐diamine are important contact allergens in hairdressers 13‐15 . In line with this, a recent study reports the frequency of patch test positivity to p ‐phenylenediamine to be 20.4% among hairdressers with contact dermatitis 12 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is in accordance with the previous findings that hair dye product ingredients such as p ‐phenylenediamine and toluene‐2,5‐diamine are important contact allergens in hairdressers 13‐15 . In line with this, a recent study reports the frequency of patch test positivity to p ‐phenylenediamine to be 20.4% among hairdressers with contact dermatitis 12 …”
Section: Discussionsupporting
confidence: 92%
“…We have previously reported based on the FROD data that the incidence of occupational ACD in Finnish hairdressers is 8.33/10 000 person years, 3 and that of CU is 0.91/10 000 person years, whereas the incidence of any OSD was 16/10 000 person years 11 . By comparison, a study on Italian hairdressers reported an estimated incidence of contact dermatitis of 18.4 per year on 10 000 workers, and that of occupational contact dermatitis 7.4 per year on 10 000 workers 12 . In the present analysis, ACD was diagnosed in 54%, whereas ICD was diagnosed in 44% of hairdressers with OSD.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Hairdressers were the second most common occupational group in our series. Hairdresser apprentices were almost as frequently sensitized to hairdresser chemicals as professionals in our study, accounting for the young age and early onset of OACD, a well‐defined feature for hairdressers 29‐32 As an exception to the literature, 30‐36 male patients predominated among hairdressers in our series because men are more frequently employed as hairdressers in Turkey. Atopics were slightly more frequent among hairdresser apprentices than professionals, supporting the so‐called “healthy worker effect,” which indicated those who leave their job at an early stage of occupation due to atopy‐related morbidity 30,34 …”
Section: Discussionmentioning
confidence: 53%
“…Ammonium persulfate (or AP) is one of the main culprits of ACD in hairdressers; this has been demonstrated on several series in which this allergen has shown positive results in a greater proportion of hairdressers when compared with controls and customers 1‐3 . ACD in hairdressers is commonly observed as hand eczema, whereas other topographies are affected in a lower proportion of patients, which makes the use of gloves an important part of the preventive measures 4 .…”
Section: Discussionmentioning
confidence: 99%